Memberdayakan Masyarakat dalam Deteksi Dini Tumbuh Kembang Anak menggunakan Aplikasi Primaku - Nurlailis Saadah; Budi Joko Santosa; Rahayu Sumaningsih; Budi Yulianto (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
Stunting is a condition of failure to thrive in toddlers due to chronic malnutrition so that children are shorter for their age. It occurs since the baby is in the womb but only appears after the child is 2 years old. On February 2020 data of Baleasri Village, from 57 children under five, there were 15 children whose body weight was thin (-2 and -3 Standard Deviation) and in the stunting category, although every month, mothers of toddlers have weighed their toddlers to the Posyandu. With data that still some toddlers whose growth and development are not optimal, it is necessary to carry out community service, the Community Partnership Program (PKM). Implementation of community empowerment /mothers of toddlers and health cadres is a means to learn about health in the form of face-to-face in groups. The aim is to increase knowledge and skills regarding early detection Children's growth and development using the PrimaKu application so that it is easier and more practical, can be done anytime and anywhere. This training was attended by ± 40 people and facilitated by lecturers/servants from the Midwifery Study Program Magetan, Ministry of Health Surabaya and students. The implementation of the training according to the agreement between the village midwife, mothers of toddlers and health cadres was carried out in the morning at 08.0-12.00 WIB. Frequency of 4 meetings. The results of the training implementation from the first, second, third and fourth meetings showed that the pretest results were 65% good and 35% very good. The post test results obtained 42.5% good and 57.5% very good which means there is an increase in the results. This training is very useful for mothers of toddlers and health cadres. It is recommended that this training activity be continued in different locations for villages in the Ngariboyo District and furthermore. can be scheduled for other villages in different sub-districts in Magetan Regency.